IS THE BRICS NEW DEVELOPMENT BANK A FLEDGLING ALTERNATIVE TO THE WORLD BANK? - A. Vazquez (BRICS Law Journal)
In 2001, the world began talking about BRIC – Brazil, Russia, India and China – as a potential powerhouse in the world economy. After the 2008 international financial crisis, BRIC gained prominent momentum and the world saw them as a serious actor to be watched. Today, BRICS (South Africa became a member of the bloc in 2010) are being closely watched because there is no certainty as to their future.The Shanghai-based New Development Bank was launched in this context and in answer to the institutional crisis that the world observed with concern when US-guided international economic institutions could not lead the way out of the 2008 crisis and into recovery.While each country around the globe lives its own domestic reality, the Trump phenomenon in the United States has erupted on the international stage and is proving to lead the still largest economy in the world onto the opposite path of the one set by the United Nations in its 2030 Agenda for Sustainable Development.These events as well as the roles played by the UN and the G20 are the subject of this article. They are analyzed in order to provide a framework from which to answer the following questions: Is the Shanghai-based New Development Bank a fledgling alternative to the World Bank, and are the BRICS a possible alternative to a more cooperative future?